Diskursus Digital dan Penjualan Kendaraan Listrik di Indonesia: Pendekatan Netnografi - Muhammad Farouq Rosyadi; Donny I Maramis; Revi Alvino; Ovalia Rukmana (Publikasi Indonesia, 2026)
The growth of electric vehicles in Indonesia is influenced not only by government policies and industrial readiness, but also by public perceptions shaped through digital media. This study explores the role of electric vehicle review videos on YouTube in shaping consumer perceptions and their relation to the development of electric vehicle sales in Indonesia. The study employs a netnographic approach by analyzing comment sections from three electric vehicle review videos on YouTube, combined with official sales data from the Indonesian Automotive Industry Association (GAIKINDO) for the 2023–2025 period and interviews with electric vehicle owners. The findings show that YouTube discussions are largely driven by practical and rational considerations, such as price, total cost of ownership, driving range, and charging infrastructure. Although the national automotive market experienced a slowdown, the market share of electric vehicles continued to grow. Interview results indicate that YouTube review videos mainly serve as information sources and tools for brand comparison, while final purchase decisions are more strongly influenced by mobility needs, government policies, and long-term considerations regarding electric vehicle technology. This study concludes that YouTube electric vehicle review videos support the consumer decision-making process, but do not directly determine sales growth.